Plant membrane and vacuolar transporters (CABI, 2008)
This book contains 14 chapters that evaluate the current knowledge, state of art and future prospects of plant membrane and vacuolar transporters in relation to plant productivity and quality improvement. The role of transporters, the mechanisms of uptake, accumulation or transport of potassium, calcium, nitrate, ammonium, sulfate, phosphate, iron, manganese, silicon, heavy metals, sugars, polyols, amino acids and secondary metabolites, the proteomic analysis of vacuolar membrane, and the elemental biofortification of crop plants are emphasized. The book is intended for scientists, researchers, students, planners and industrialists working in the area of biotechnology, plant agriculture, agronomy, horticulture, plant physiology, molecular biology, nutritional biology, plant sciences and environmental sciences.